As good as the first time - Jackson, K. M. (Jackson, K. M. Sugar Lake novel., 2018)
With her big-city career and relationship in sudden free fall, Olivia Gale isn<U+2019>t sure where she belongs. So when her help is needed at Goode <U+02BC>N Sweet, the family bakery in Sugar Lake, she jumps at the chance to indulge her pie-making hobby while getting her life back on track. Olivia<U+2019>s not looking for any distractions. Even if the boy who once left her without a word is now a grown man with intriguing secrets<U+2014>and the same tempting hold on her heart . . . A firefighter and single dad, Clayton Morris is trying hard to fix his past mistakes. He thought he was doing the right thing by leaving Olivia<U+2014>and now he<U+2019>s sure he has nothing to offer the accomplished woman she<U+2019>s become. But ignoring the sparks between them is impossible. And as unexpected surprises and hard choices endanger their fragile reunion, they<U+2019>ll have to decide which direction to take if they want to find the road back to love . . .